Spinal motor neuronal organisation of selected local freshwater fishes in relation to median fin innervations / Kwong Soke Chee - Kwong, Soke Chee (2012)
Fish fins are appendages which represent the limbs in higher vertebrates. In general, fish moves in the water by body undulation with the assistance of fins. To date, most of the studies focused on the innervations of limbs especially in mammals, such as rats, cats and monkeys. On the contrary, understanding on the innervations of the fish fin is still at its infancy as studies on the relevant field are relatively scarce. Hence, this study aimed to fill the knowledge gap, i.e. to investigate the organisation of spinal motor neurons in relation to the distribution of the median fins. For comparison purposes, four species of juvenile fishes utilised in this study were divided into two groups, namely (i) fish with long and continuous dorsal fin (Channa micropeltes, toman and Clarias sp., keli), and (ii) fish with short and non-continuous dorsal fin (Mystus nemurus, baung and Pangasius sp., patin). Spinal cord tissue obtained from three different representative segments along the rostro-caudal axis were processed histologically and stained using three neurohistological staining techniques including H&E, Nissl as well as Lillie’s Variant of the Weil-Weigert prior to light microscopy level observation. The organisation of motor neurons was correlated with the distribution of fins. Cell column organisation characterised the location of motor neurons into seven cell columns, namely intermediolateral (IL), dorsomedial (DM), ventromedial (VM), central (C), ventrolateral (VL), dorsoventral (DV) and retrodorsolateral (RDL) cell columns. It was observed that median motor neurons (IL, DM and VM cell columns) outnumbered central (C cell column) and lateral motor neurons (VL, DL and RDL cell columns) at all rostral, median, and caudal region of the fish body trunk. Medial motor neurons (IL and DM cell columns) were found in all three segments; thus, were probably innervating the body trunk, for instance to aid in body undulation. On the contrary, DL motor neurons were found only at the dorsal fin area of Clarias sp. and Pangasius sp.; thus, were probably innervating the particular fin. To further investigate the innervations of caudal fin muscles through HRP histochemistry, Clarias sp. with rounded caudal fin and Pangasius sp. with forked caudal fin were selected from each group. The nerve trunks at the caudal fin were transected and soaked in 50% HRP solution. After two days, each fish was sacrificed and its spinal cord was freeze-sectioned using cryostat. The sections were stained using DAB Liquid Enhanced Substrate kit to reveal the motor neurons containing HRP in the cytoplasm which appeared as brownish precipitations. Most of the motor neurons innervating Clarias sp. rounded caudal fin were located medially at IL, DM and VM cell columns. In contrast, the motor neurons innervating forked caudal fin of Pangasius sp. were located mostly at the ventral areas, namely VM and VL cell columns. The differences of the motor neuronal organisation between the two species could be credited to further muscle differentiation in the caudal fin muscle layers of Pangasius sp., which exhibited more complicated organisation than that of the Clarias sp. In conclusion, the findings of this study were in agreement with the existing literature that medial motor neurons (IL and DM cell columns) innervate body trunk while more laterally located motor neurons (VM, VL and DL cell columns) innervate distal structure, in this case the fins. Future research can focus, specifically, on the innervations by individual nerve trunk or innervations of individual muscle and/or the research can be conducted at different stages of life cycle of the fish.